CARDIOGENIC SHOCK FOLLOWING ACUTE MYOCARDIAL INFARCTION: A RETROSPECTIVE OBSERVATIONAL STUDY - Sadeghi, Roxana; Kachoueian, Naser; Maghsoomi, Zohreh; Sistanizad, Mohammad; Soroureddin, Zahra; Akbarzadeh, Mohammad Ali (International Journal of Cardiovascular Practice)
Introduction: Cardiogenic shock is a sudden complication that occurs in 5 to 10% of patients with acute myocardial infarction. According to statistics, mortality and morbidity from this event, despite all hospital care, are approximately 70-80%.Methods: This study was conducted over three years (2012 to 2014) in 28 cases of acute myocardial infarction, which was complicated by cardiovascular shock, before or after admission. We compared the outcomes of patients according to the treatment strategy, thrombolytic therapy, primary percutaneous coronary intervention (PCI), or other medical stabilization. The 30-day follow-up was the first endpoint, and the 3- month follow up was the second endpoint of the study.Results: 28 patients with cardiogenic shock included in this study. The mean (± SD) age of the patients was 62.99 ± 13.99 years. The median time to the onset of shock was 648.75 ± 1393.58 minutes after infarction. Most of the patients who underwent coronary angiography had 3-vessel or left main involvement. Two patients missed in follow up and five (80%) patients who received thrombolytic therapy passed away. Nine (100%) patients in the medical stabilization group and six patients (50%) underwent primary PCI group passed away too. The mortality in the primary PCI group was significantly lower than the other groups (P = 0.04).Conclusion: Although cardiogenic shock is a potential risk of early death, it is important that the thrombolytic in these patients doesn't increase survival and the primary PCI is more effective than thrombolytic agents.